AFFIRMING PANCASILA STUDENTS’ PROFILES THROUGH DIFFERENTIATED LEARNING INSTRUCTION: A QUALITATIVE STUDY OF THE INDONESIAN HISTORY SUBJECT AT SENIOR HIGH SCHOOL - Moch. Dimas Galuh Mahardika (Jurnal Historica, 2026)
The Merdeka Curriculum (Kurikulum Merdeka), which currently underpins Indonesia’s educational system, emphasizes independent learning grounded in national character values, as articulated in the concepts of Merdeka Belajar and the Pancasila Student Profile (Profil Pelajar Pancasila). Informed by the educational philosophy of Ki Hajar Dewantara, the curriculum incorporates the principles of freedom, nationalism, natural law, culture, and humanity. In classroom settings, especially in history education, the Merdeka Curriculum aims to address students' diverse learning characteristics, including learning styles, behavioral tendencies, and cognitive capacities. This pedagogical approach is known as differentiated learning instruction (Pembelajaran Berdiferensiasi). This study employs a descriptive qualitative method to explain the implementation of differentiated learning in Indonesian History classes at SMAS Al-Izzah Batu, in accordance with the principles of the Merdeka Curriculum and the Pancasila Student Profile. The research sample contains 18 students. The findings are presented through descriptive analysis, supporting documents, and photographs depicting differentiated learning activities conducted in grade XI during lessons on the topic “The Impact of Colonialism on Everyday Life.”